Macroeconomics : a European text - Burda, Michael C.; Wyplosz, Charles (New York : Oxford University Press, 2001)
The book provides a comprehensive analysis of modern macroeconomics withih both a European and a global context. Fully revised and updated, this third edition includes new material on economic growth, labour markets and unemployment, money supply, inflation, supply-side policy, asset markets, the 'new economy', EMU, and the architecture of the international monetary system.
Includes bibliographical references and index.
rpm 30/10/13
Loans
Keywords: Macroeconomics; Europe -- Economic conditions